Preclinical and Clinical Applications of Photobiomodulation Therapy in Sperm Motility: A Narrative Review: Effect of Photobiomodulation Therapy on Sperm Motility - poorhassan, Mahnaz; Gholaminejhad, Morteza; Ahmadi, Houssein; Mehboudi, Leila; Chahar Kameh, Mahdis; pirani, Maryam; Hasanzadeh, Gholamreza (Journal of Lasers in Medical Sciences, 2022)
About 50% of infertility problems are related to male factors and reduced sperm motility. The important factor that affects the structure and function of sperm is reactive oxygen species (ROS), and over-concentration of ROS reduces the quality and motility of sperm. Photobiomodulation therapy (PBMT) using red to near-infrared (NIR) light is useful in oxidative stress restoration. It plays a therapeutic role in disorders such as asthenospermia, oligospermia cases, and cryopreserved sperm. It also enhances the metabolic capacity of sperm and increases the low-level and nonharmful intracellular content of Ca2+, nitric oxide (NO), and ROS in the stressed cells. Likewise, it modulates survival intracellular pathways and maintains the motility, viability, DNA, and acrosome integrity of sperm. This article reviews the state-of-the-art preclinical and clinical evidence regarding the efficacy of semen PBMT.